Uranyl nitrate crystallizer performance with changing solution level. Issue 5 (May 2019) - Nadezhdin, Igor S.; Gozhimov, Alexandr I.; Goryunov, Alexey G.; Colombo, Simone; Manenti, Flavio
Abstract: This manuscript described a dynamic simulation of uranyl nitrate crystallization in a linear crystallizer. Furthermore, a mathematical model of the crystallizer supply system was developed with a related control algorithm; the model contained two piston feeders. The results showed the crystallization process's sensitivity to the solution level in the crystallizer. An expression for calculating the performance of the crystallizer was proposed. That expression allowed us to understand that the accuracy of the liquid phase level (to avoid the crystallizer's performance decreasing by more than 5%) should be in the range of ±4% of the crystallization section height. For this, we developed a control algorithm for the supply system to support operability. This algorithm allowed us to maintain a specified level of mother solution in the crystallization area and provided an asynchronous operation mode for the piston batchers. Furthermore, this paper described how the developed mathematical model and the proposed control system, i.e., the envisaged recommendations, can be used to optimize the process during the design and adjustment of equipment.